Plasmacytoid variant urothelial carcinoma of the bladder: effect of radical cystectomy and chemotherapy in non-metastatic and metastatic patients - Sorce, Gabriele; Flammia, Rocco Simone; Hoeh, Benedikt; Chierigo, Francesco; Horlemann, Benedikt; Würnschimmel, Christoph; Tian, Zhe; Graefen, Markus; Terrone, Carlo; Gallucci, Michele; Chun, Felix K H; Saad, Fred; et al. (World journal of urology, 2022)
PURPOSE: Data about optimal management of plasmacytoid (PCV) bladder cancer patients are extremely scarce and limited by sample size. We focused on PCV bladder cancer patients to explore the effect of radical cystectomy (RC) and chemotherapy in non-metastatic (T 2-4N0-3M0), as well as in metastatic (TanyNanyM1) subgroups. METHODS: Using the Surveillance, Epidemiology and End Results database (2000-2016), we identified 332 PCV patients with muscle-invasive disease or higher (≥ T2N0M0). Kaplan-Meier plots and Cox regression models addressed cancer-specific mortality (CSM). RESULTS: In 332 PCV patients, median age was 68 years (Interquartile range [IQR]:58-76). Of those, 252 were non-metastatic patients (76%) vs 80 were metastatic patients (24%), at presentation. Of non-metastatic patients, 142 (56%) underwent RC and 131 (52%) underwent chemotherapy. Chemotherapy did not improve CSM in non-metastatic PCV. Conversely, RC was associated with lower CSM (hazard ratio [HR]: 0.51, p = 0.002). Median CSM-free survival was 48 vs 38 months for RC treated vs RC not treated. Of metastatic patients, 22 (28%) underwent RC and 42 (52%) underwent chemotherapy. Both chemotherapy and RC improved CSM in metastatic PCV. Median CSM-free survival was 12 vs 7 months for RC treated vs RC not treated (HR: 0.27, p < 0.001). Median CSM-free survival was 11 vs 4 months for chemotherapy exposed vs chemotherapy naïve (HR: 0.32, p = 0.002). CONCLUSIONS: Although RC resulted in lower CSM, chemotherapy failed to show that effect in non-metastatic PCV patients. Conversely, both chemotherapy and RC resulted in statistically significantly lower CSM in metastatic PCV patients.
Keywords: cystektomie; karcinom z přechodných buněk; Plasmacytoid; lidé; Radical cystectomy; program SEER; Chemotherapy; Cancer; Bladder; Urinary Bladder Neoplasms; Urinary Bladder; Aged; Carcinoma, Transitional Cell; nádory močového měchýře; močový měchýř; SEER Program; Cystectomy; senioři; Signet ring cell; Humans